All the pretty things : a memoir : the story of a southern girl who went through fire to find her way home - Wadsworth, Edie (Tyndale Momentum, an imprint of Tyndale House Publishers, Inc., 2016)
The story of "Edie's soul-searching journey out of the rubble of her childhood, through the devastating choices of her adulthood, and into a life of healing and forgiveness that she never dreamed possible"--Page 4 of cover.